The perceived role fit of women and men academics: evidence from the social sports sciences - Lesch, Lara; Scharfenkamp, Katrin; Wicker, Pamela (Frontiers in Psychology, 2023)
The underrepresentation of women in academia is often explained with the presence of gender stereotypes and the perception that women fit the role of an academic to a lesser extent. Based on social role theory and role congruity theory, this study investigates and estimates the perceived role fit of women and men academics in the social sports sciences. Data were collected with a quantitative online survey. The sample (n=792) includes individuals who study or work in sports economics, sport management, or sport sociology (referred to as social sports sciences). The questionnaire included items that reflect attributes of an ideal-typical academic as well as women and men academics in four dimensions, i.e., leadership, research methods, media visibility, and research topics. In the first step, these items were used to estimate a total role fit index for both women and men academics, as well as indices for all dimensions. In a second step, regression analyses were used to examine how respondents' individual characteristics (e.g., discipline, career stage, gender, presence of role models) are related to their perceived role fit indices and the differences in the perceived role fit. The role fit index ranges from 0-1, and women have a higher total role fit than men (0.77 vs. 0.75). The results suggest that women in the social sports sciences are perceived as a better fit to the role of an academic. In contrast to role congruity theory, women's leadership fit is higher than men's fit in this dimension (0.79 vs. 0.72). Regarding the associations of individual characteristics, professors seem to perceive a lower role fit for both genders compared to students. Furthermore, the difference between the perceived role fit of men and women is smaller for women respondents. Having a woman role model leads to a higher fit of women academics in the leadership dimension.